2018
DOI: 10.1371/journal.pone.0204489
|View full text |Cite
|
Sign up to set email alerts
|

HIV test uptake and related factors amongst heterosexual drug users in Shandong province, China

Abstract: BackgroundIn China, the mode of HIV transmission and the types and routes of drug use have changed in the past decade. HIV testing amongst drug users needs further improvement.MethodsInterviewer-administered questionnaires were used for data collection amongst 600 heterosexual drug users from the community and a municipal detention centre, where criminal suspects are supervised. Descriptive statistics, univariate analysis and multilevel logistic regression analysis were used to identify the factors associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
1
11
3
Order By: Relevance
“…We found a low HIV and syphilis testing uptake among heterosexual STD clinic patients in China. This rate is much lower than previously reported in Zambia, 19 Botswana 20 and South Africa, 21 whereas other studies showed that social stigma against HIV and STD, 22 fear of testing 23 and lack of testing information 24 are main contributors of limiting HIV and syphilis testing, our study found that the most common barrier in this sample of Chinese heterosexual STD clinic patients was a perceived low risk of HIV and syphilis infection. This highlights the importance of improving knowledge and awareness related to HIV and syphilis infection among heterosexual STD clinic patients.…”
Section: Discussioncontrasting
confidence: 81%
“…We found a low HIV and syphilis testing uptake among heterosexual STD clinic patients in China. This rate is much lower than previously reported in Zambia, 19 Botswana 20 and South Africa, 21 whereas other studies showed that social stigma against HIV and STD, 22 fear of testing 23 and lack of testing information 24 are main contributors of limiting HIV and syphilis testing, our study found that the most common barrier in this sample of Chinese heterosexual STD clinic patients was a perceived low risk of HIV and syphilis infection. This highlights the importance of improving knowledge and awareness related to HIV and syphilis infection among heterosexual STD clinic patients.…”
Section: Discussioncontrasting
confidence: 81%
“…This rate is much lower than previously reported in Zambia [15], Botswana [16] and South Africa [17]. Whereas other studies showed that social stigma against HIV and STD [18], fear of testing [19] and lack of testing information [20] are main contributors of limiting HIV and syphilis testing, our study found that the most important barriers in this sample of Chinese heterosexual STD clinic attendees were a perceived low prevalence of HIV and syphilis. This highlights the importance of improving knowledge and awareness of HIV and syphilis infection among heterosexual STD clinic attendees on increasing the acceptance of PITC services.…”
Section: Discussioncontrasting
confidence: 90%
“…[27][28][29][30] Studies in the Asia-Pacific region indicated that HIV testing among PWUD was associated with sociodemographic characteristics, history of injection drug use, sexually transmitted infections (STIs), history of incarceration and HIV-related knowledge. [31][32][33] Under the Cambodian National Strategic Plan IV (2015-2020), individuals at high risk for HIV, including PWUD, are recommended to have an HIV test every 6 months to ensure early diagnosis and ongoing health literacy on HIV prevention. 34 However, currently, there is no published information about HIV testing among PWUD in Cambodia.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%